1975
DOI: 10.1002/aja.1001430203
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction of the canyon bat, Pipistrellus hesperus, in Southwestern United States

Abstract: The reproductive biology of the bat Pipistrellus hesperus was investigated histologically using animals obtained from nature at monthly intervals throughout the year. The female shows proestrous morphological changes in late summer and autumn, which continue until early spring. Insemination is probably effected several times during proestrous, since both sexes are intermittently active throughout this period (August--April). Permanent arousal from torpor and return to normal metabolism in the spring results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 24 publications
4
32
0
Order By: Relevance
“…The asynchrony of primary and secondary sexual functions is a common feature of the hiber¬ nating bats (Miller, 1939;Pearson et al, 1952;Krutzsch, 1961Krutzsch, , 1975Racey, 1974;Racey & Tarn, 1974;Gustafson, 1976Gustafson, , 1979Bernard, 1986;Krutzsch & Crichton, 1986) but has not previously been reported for a tropical bat, while even in temperate-zone bats in which asynchrony does occur the separation is never as dichotomous as it would appear to be in the common sheath-tail bat. Clearly in this species the separation enables the insemination of females close to ovulation, but an interesting question is why the burden of sperm storage falls on the male with the consequential complications of the separation of primary and secondary sexual functions.…”
Section: Discussionmentioning
confidence: 99%
“…The asynchrony of primary and secondary sexual functions is a common feature of the hiber¬ nating bats (Miller, 1939;Pearson et al, 1952;Krutzsch, 1961Krutzsch, , 1975Racey, 1974;Racey & Tarn, 1974;Gustafson, 1976Gustafson, , 1979Bernard, 1986;Krutzsch & Crichton, 1986) but has not previously been reported for a tropical bat, while even in temperate-zone bats in which asynchrony does occur the separation is never as dichotomous as it would appear to be in the common sheath-tail bat. Clearly in this species the separation enables the insemination of females close to ovulation, but an interesting question is why the burden of sperm storage falls on the male with the consequential complications of the separation of primary and secondary sexual functions.…”
Section: Discussionmentioning
confidence: 99%
“…In the Mpumalanga bats the amount of sperm present in the females did not increase from May to July, suggesting a possible loss of spermatozoa. It has long been argued that for some bat species additional copulation during the hibernation period and even after arousal in the spring may be necessary to assure fertilization, because the initial spermatozoa may either lose their capacity to fertilize or be expelled from the female reproductive tract (Guthrie 1933;Guthrie & Jeffers 1938;Krutzsch 1975). Guthrie (1933) mentioned that muscular activity result in the expulsion of uterine contents into the vagina and to the outside and further that there is a reduction of sperm due to the phagocytic behaviour of the leucocytes.…”
Section: Sperm Storagementioning
confidence: 99%
“…Guthrie (1933) mentioned that muscular activity result in the expulsion of uterine contents into the vagina and to the outside and further that there is a reduction of sperm due to the phagocytic behaviour of the leucocytes. It thus seems that activities such as flying around may result in the emptying of the sperm and other contents from the female tract, and that repeated winter foraging might each time empty the tract of sperm (Krutzsch 1975). Racey (1975) also referred to factors that may be involved in the removal of spermatozoa from there storage organs, such as muscular contractions, enzymatic dissolution, phagocytosis by leucocytes or epithelial cells, or the active entry of sperm into the epithelial and subepithelial tissues.…”
Section: Sperm Storagementioning
confidence: 99%
See 1 more Smart Citation
“…The male patterns are identified by types in Table 1 and by species in Table 2. In the Type I pattern, the male reproductive cycles are interrupted annually by Krutzsch (1975) Pipistrellus pipistrellus Courrier (1923aCourrier ( , b, 1926bCourrier ( , 1927; Racey & Tarn (1974) Rhinolophusferrumequinum Courrier (1927); Vignoli (1930) Rhinolophus hipposideros Courrier (1923bCourrier ( , 1927; Gaisler & Titlbach (1964); Gaisler (1966) Ib Eptesicusfuscusfuscus Christian (1956) (eastern U.S.A.) Myotis blythi oxygnathus Koceva (1970) Myotis capaccinii Courrier (1927) Myotis grisescens Miller (1939) Myotis I. lucifugus Miller (1939); Gustafson (1975aGustafson ( , 1976) Myotis myotis Courrier (1923bCourrier ( , 1927 (1923b, 1927) * Based on the dental formula of this species, it has recently been suggested that the genus Miniopterus be placed in a separate family, the Miniopteridae (Mein & Tupinier, 1977). In this summary, miniopterines are still treated as vespertilionids.…”
Section: Patterns Of Male Cyclesmentioning
confidence: 99%